Separation performance of supercritical carbon dioxide extraction column for crude palm oil processing: observation using process simulator - Lim, Chee Siang (2005)

(untitled)
Separation behaviour of crude palm oil (CPO), which contains principally triglycerides, fatty acids and valuable minor components such as alpha-tocopherol and beta-carotene, with supercritical carbon dioxide was observed using process simulator AspenÂ® Plus. Solubility of palm oil components in supercritical CO2 extraction column was calculated by Redlich-Kwong â€“Aspen equation of state. Process flow diagram for the CPO processing by supercritical CO2 extraction column was successfully constructed to evaluate the separation performance. The effects of reflux ratio,stage number of extraction column and solvent-to-feed (S/F) flow rote ratio on the extract and raffinate product purities as well as the recovery of palm oil TG were studied at 373K and 20-30Mpa.